Acute myocardial infraction and pulmonary embolism in a same patient with COVID -19: a rare association - Preet Randhawa; Parminder P. Singh; Nirmal Guragai; Parminder Kaur; Balraj Singh; Jasjit S. Walia (Greater Baltimore Medical Center, 2021)
Coronavirus disease-2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 is associated with a hypercoagulable state leading to increased incidence of thromboembolism. However, it is exceedingly rare to see presence of both arterial and venous thromboembolism simultaneously. Herein, we report an unusual presentation of a 39-year-old male with recently diagnosed COVID -19 who initially had acute myocardial infarction secondary to thrombotic occlusion of right coronary artery followed by acute pulmonary embolism. Health care providers should be aware of this uncommon yet possible co-existence of two life-threatening manifestations in order to prevent fatal consequences.